Analisis Semantik Leksikal al-Zamakhsharī Terhadap Frasa "Personal Branding" Nabi Mūsā (AS) dalam al-Qur`ān: Al-Zamakhsharī’s Lexical-Semantic Analysis of the “Personal Branding” Phrase of Prophet Mūsā (AS) in the Qur’ān - Rafi Dinilhaq; Novizal Wendry; Nandi Pinto (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
This study is prompted by the presence of particular phrases in the Qurʾān that highlight Prophet Mūsā’s distinctive attributes, what can be termed his “personal branding.” These phrases provide a lens through which to compare the Qurʾānic portrayal of Prophet Mūsā’s character with commonly held perceptions. The research aims to uncover the deeper meanings behind these personal branding elements and to encourage reflection on their significance. Employing a qualitative methodology, the inquiry centers on verses narrating Prophet Mūsā’s story. Al-Zamakhsharī’s semantic theory guides the examination of the linguistic features of these phrases, while Peter Montoya’s “The Eight Laws of Personal Branding” helps classify the aspects that shape Prophet Mūsā’s personal brand. The findings indicate that Prophet Mūsā’s personal branding is established through four key dimensions: specialisation, leadership, personality, and differentiation. These facets emerge from eight Qurʾānic descriptors—al-Qawiy, al-Amīn, Mukhlaṣ, Rasūl, Nabiyyā, Ghaḍbān, al-Kalīm, and al-Aʿlā. The study concludes that the narrative verses of the Qurʾān can be analyzed not only for their moral guidance but also for the insights they offer into the personal branding of their central figures.